El pasaje antimaniqueo de "Confesiones" III y su "público maniqueo" - Kotzé, Annemaré ca. 20./21. Jh. (Avgvstinvs, 2024)
The article is an analysis of Confessions 3 .6.10 to 3.10.18 to support an argument that many strategies in Augustine's masterpiece are eminently suited to communicate with a Manichaean audience and designed to convince such an audience of the errors of Manichaeism. In Book 3 the narrative reaches the stage of Augustine's life where he joins the Manichees. The description of the encounter presented here, however, is much more than the communication of information on this crucial stage in his spiritual joumey. The passage is generally described as strongly anti-Manichaean, but I argue that the argumentative and emotional tone of the passage combined with the amount of space spent on a few core aspects of Manichaeism make the passage an effective protreptic directed at a specific category of "Manichaean" readers.